Feeding Ecology of Elusive Caribbean Killer Whales Inferred From Bayesian Stable Isotope Mixing Models and Whalers’ Ecological Knowledge - Kiszka, Jeremy J.; Caputo, Michelle; Méndez-Fernandez, Paula; Fielding, Russell (Frontiers in Marine Science, 2021)
Investigating the feeding ecology of marine predators is critical for understanding their roles and functional importance in ecosystems. However, assessing the diet of large and wide-ranging predators can be challenging, particularly in the case of rare and elusive species. Killer whales (Orcinus orca) are the largest apex predators in global oceans, but very little is known about their feeding ecology in tropical ecosystems, particularly in the Caribbean Sea. Killer whales are distributed throughout the Caribbean, and are a regular target of artisanal whalers in St Vincent and the Grenadines (West Indies). Here we investigate the feeding ecology of Caribbean killer whales using a combination of stable isotope analysis (δ15N, δ13C) and traditional ecological knowledge (TEK) data from whalers operating from St. Vincent. Potential prey data from the Caribbean region included large pelagic teleosts, sea turtles, oceanic sharks, cetaceans, and oceanic cephalopods. Mixing models suggest that the contribution of odontocete cetaceans to the diet of killer whales is the most important (overall mean contribution: 60.4%), particularly mesopelagic delphinids (Lagenodelphis hosei; 26.4%, SD=0.14), large teuthophageous odontocetes (Physeter macrocephalus, Globicephala macrorhynchus; 20.0%, SD=0.14), and epipelagic delphinids (Stenella attenuata; 14%, SD=0.14). Oceanic sharks (Carcharhinus longimanus) had a contribution of 17.0% of the diet of killer whales (SD=0.13), and other potential prey had a relatively marginal contribution. TEK data suggest that whalers believe killer whales feed almost exclusively on cetaceans, particularly odontocete species that they hunt (e.g., G. macrorhynchus). Stable isotope and TEK data were consistent to some extent, although TEK data are qualitative and based on a limited number of observations. Despite some limitations (including sample size for both methods), this study highlights the value of combining independent data sources and methodologies to investigate the ecological roles of marine predators in data-poor regions.